It’s not all about the money: narratives on emotions after a sudden death in family businesses - Heinonen Jarna; Ljunggren Elisabet (Taylor & Francis, 2022)
Emotions matter in businesses but have received little research attention. The socioemotional wealth (SEW) perspective is applied to gain a better understanding of the role of emotions in family businesses in the case of a sudden death of a key family and business person. The study contributes methodologically by applying a novel combination of case study and narratives of two families and their firms after experiencing a sudden death. The study contributes theoretically to the family business literature on emotions by providing a multilevel perspective and highlighting how the family business and the business family intertwine in a highly emotional situation, and to the SEW approach by offering a more nuanced understanding of the role emotions play over time. Emotions shape the decisions families make for the firm, but the firm also provides an emotional arena for family members to cope with their struggles. Employees are a part of the SEW considerations as families balance their moral obligation to protect the interests of non-family employees. To better cope with a crisis, family members should be well informed of or involved with the family firm even if they do not actively work there.